A method for preparing silicotungstic acid by white tungstic acid method
Patent Information
- Application Number
- CN202611363198.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的在于提供一种白钨酸法制备硅钨酸的方法,旨在解决现有硅钨酸制备工艺存在的安全风险高、原料成本高、产物硅钨比难以精准控制、杂质易共引入及环保性差的技术问题,实现硅钨酸的清洁化、规模化、低成本生产
1、本发明不使用乙醚等易燃易爆、具有毒性的有机溶剂,消除了传统醚萃工艺固有的爆炸风险与职业健康危害,避免了有机废液的产生;同时摒弃氨水与阳离子交换树脂工艺,通过双极膜电渗析完成阳离子转换,无需进行树脂洗脱与再生操作,大幅降低水资源消耗,从源头减少氨氮废水与高盐废液排放,契合清洁化工的技术发展方向。
Smart Images

Figure CN122916149A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fine chemical technology, specifically relating to a method for preparing silicotungstic acid using the scheelite method. Background Technology
[0002] Tungstosilicic acid is a heteropolyacid compound with a Keggin structure and the molecular formula H4SiW. 12 O 40 ·nH₂O, with its anionic structure consisting of 12 tungsten-oxygen octahedra surrounding a central silicon-oxygen tetrahedron, exhibits characteristic acidity, redox properties, and thermal stability. Silicotungstic acid, as an important catalytic material, is widely used in petrochemicals, organic synthesis, and biomass conversion, catalyzing reactions such as esterification, oxidation, and hydrogenation. It can also be used as a biochemical reagent and mordant in analytical testing and mineral processing.
[0003] One of the mainstream preparation processes for silicotungstic acid is the sodium tungstate acidification and diethyl ether extraction method: (Refer to...) Figure 1 Sodium tungstate and sodium silicate are prepared into an aqueous solution and heated to boiling. Hydrochloric acid is added dropwise to the system for acidification, followed by extraction and separation of silicotungstic acid using a large amount of diethyl ether. Finally, hydrated silicotungstic acid is obtained through multiple dissolutions and evaporations. Although this process can produce qualified silicotungstic acid, it has significant technical limitations: the reaction process uses a large amount of acid, and the diethyl ether used is volatile, toxic, flammable, and explosive, posing high safety risks during production. It also generates a large amount of acidic and organic waste liquid, causing significant environmental pollution and making it unsuitable for large-scale industrial production.
[0004] Another known preparation route is the ammonium metatungstate method: refer to Figure 2 The process begins with ammonium metatungstate as the starting material. Silicic acid and ammonia are added to the system and the mixture is heated to produce an ammonium silicotungstate salt solution. Ammonium ions are then removed using a strongly acidic cation exchange resin to obtain a silicotungstic acid solution, which is finally concentrated by evaporation to obtain the final product. This process avoids the use of diethyl ether, but it also has several technical shortcomings: 1. The ammonium metatungstate raw material requires high purity, and during the reaction, silicon-oxygen tetrahedra are difficult to embed into the central sites of the metatungstic acid anions, making it difficult to precisely control the silicon-tungsten molar ratio of the product, resulting in poor product composition stability. 2. The elution and regeneration process of the cation exchange resin consumes a large amount of water and generates ammonia-nitrogen-containing wastewater, leading to high environmental treatment costs. 3. Molybdenum, a byproduct of the tungsten raw material, is easily introduced into the product during the reaction, reducing product purity and affecting its catalytic selectivity and stability.
[0005] In summary, existing silicotungstic acid preparation processes suffer from technical bottlenecks in areas such as production safety, environmental friendliness, product composition control, and raw material impurity compatibility, hindering the clean and large-scale industrial production of silicotungstic acid. Developing a safe, environmentally friendly, product-proportion-controllable, and high-purity silicotungstic acid preparation method is a pressing technical problem to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing silicotungstic acid using the scheelic acid method, aiming to solve the technical problems of high safety risks, high raw material costs, difficulty in accurately controlling the silicon-tungsten ratio of the product, easy introduction of impurities, and poor environmental performance in existing silicotungstic acid preparation processes, and to achieve clean, large-scale, and low-cost production of silicotungstic acid.
[0007] On the one hand, the present invention provides a method for preparing silicotungstic acid by the scheelite method, which adopts the following technical solution: A method for preparing silicotungstic acid using scheelic acid includes the following steps: 1) Prepare an aqueous solution of sodium tungstate and react it with dilute acid to form scheelic acid precipitate. After separation and washing, disperse the scheelic acid in water to obtain a scheelic acid dispersion. 2) Add sodium silicate to the scheelic acid dispersion, control the molar ratio of silicon to tungsten to be 1:12, adjust the pH of the system to 3-4, heat and reflux to react, and obtain sodium silicotungstate solution; 3) The sodium silicotungstic acid solution is passed into a bipolar membrane electrodialysis system for cation exchange to obtain a silicotungstic acid solution.
[0008] Preferably, in step 1), the sodium tungstate is sodium tungstate dihydrate; The dilute acid is either dilute nitric acid or dilute sulfuric acid.
[0009] Preferably, in step 1), the dilute acid is slowly added to the sodium tungstate aqueous solution, and the reaction is carried out under continuous stirring at a stirring speed of 280-320 rpm. The scheelite precipitate was separated by vacuum filtration and washed with distilled water at least three times.
[0010] Preferably, in step 2), sodium hydroxide is used to adjust the pH of the system to 3-4.
[0011] Preferably, in step 2), the heating reflux reaction time is 0.8-1.2 h.
[0012] Preferably, in step 3), the cation exchange treatment time of the bipolar membrane electrodialysis system is 5-7 hours.
[0013] Preferably, in step 3), the obtained silicotungstic acid solution is subjected to evaporation and drying to obtain a solid silicotungstic acid product.
[0014] On the other hand, the present invention also provides silicotungstic acid prepared by the above preparation method, using the following technical solution: A silicotungstic acid, wherein the silicotungstic acid is a hydrated silicotungstic acid H4SiW having a Keggin structure. 12 O 40 ·nH2O, the molar ratio of silicon to tungsten is 1:(12±0.05).
[0015] In summary, the present invention has the following beneficial technical effects: 1. This invention does not use flammable, explosive, or toxic organic solvents such as diethyl ether, eliminating the inherent explosion risks and occupational health hazards of traditional ether extraction processes and avoiding the generation of organic waste liquid. At the same time, it abandons the ammonia water and cation exchange resin process, and completes the cation conversion through bipolar membrane electrodialysis, eliminating the need for resin washing and regeneration operations, significantly reducing water consumption, reducing the discharge of ammonia nitrogen wastewater and high-salt waste liquid from the source, and conforming to the technological development direction of clean chemical industry.
[0016] 2. This invention uses highly active scheelite as a reaction intermediate and constructs a silicotungstate structure through coordination self-assembly under weakly acidic conditions. The silicon-tungsten molar ratio of the product can be precisely controlled by the raw material feeding ratio, ensuring that the product forms a stable Keggin-type structure. This solves the technical problem of silicon element being difficult to embed into the anion center and large fluctuations in product composition in the existing ammonium metatungstate process, and significantly improves the uniformity of product composition and batch stability.
[0017] 3. In this invention, scheelic acid precipitation and heteropolyacid have good impurity selectivity, which can effectively avoid the co-introduction of molybdenum elements associated with tungsten raw materials into the product system. Even when the raw materials contain molybdenum impurities, high-purity silicotungstic acid products with low molybdenum content can still be obtained. This not only improves the catalytic selectivity and application stability of the product, but also reduces the purity requirements of upstream raw materials and broadens the range of raw material compatibility.
[0018] 4. This invention eliminates the steps of ether extraction and resin ion exchange, controls the liquid-solid ratio of the reaction within a reasonable range, significantly shortens the operation cycle, and reduces energy consumption and time costs. Attached Figure Description
[0019] Figure 1 Preparation of H4SiW by existing ether extraction method 12 O 40 • nH2O synthesis route diagram; Figure 2 The existing ammonium metatungstate method for preparing H4SiW 12 O 40 • nH2O synthesis route diagram; Figure 3 This is a schematic diagram of the process route for preparing silicotungstic acid according to an embodiment of the present invention; Figure 4 Silicotungstic acid H4SiW 12 O 40 ·Structural diagram of nH2O; Figure 5 The infrared spectra of silicotungstic acid and silicotungstic acid standard samples prepared in the embodiments of the present invention are shown below. Figure 6 The X-ray diffraction patterns of silicotungstic acid and silicotungstic acid standard samples prepared in the embodiments of the present invention are shown below. Figure 7 The images show the Raman spectra of silicotungstic acid and silicotungstic acid standard samples prepared in the embodiments of the present invention. Figure 8 Thermogravimetric analysis curves of silicotungstic acid and silicotungstic acid standard samples prepared in the embodiments of the present invention are shown. Figure 9 The capillary electrophoresis spectra of silicotungstic acid and silicotungstic acid standard samples prepared in the embodiments of the present invention are shown below. Figure 10 The energy dispersive spectroscopy (EDS) elemental analysis diagrams of silicotungstic acid (Spectrum 1) and silicotungstic acid standard sample (Spectrum 2) prepared in the embodiments of the present invention are shown. Figure 11 This is a comparison of the reaction process of scheelic acid in this invention and the in-situ Raman spectra of metatungstic acid in the prior art; Figure 12 Energy dispersive spectroscopy (EDS) elemental analysis of silicotungstic acid (Spectrum 3) prepared from sodium molybdate-doped raw material. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, the scope of protection of this invention is not limited to the following specific embodiments. Those skilled in the art can make several improvements and modifications without departing from the concept of this invention, and these all fall within the scope of protection of this invention.
[0021] Example This embodiment prepares silicotungstic acid according to the technical solution of the present invention.
[0022] Reference Figure 3 A method for preparing silicotungstic acid using the scheelite method, the specific steps of which are as follows: S1, preparing the solution Add 500g of sodium tungstate dihydrate (Na2WO4·2H2O) and 3000mL of distilled water to a 10000mL beaker, and stir until completely dissolved to obtain an aqueous solution of sodium tungstate; add 3000mL of distilled water to a 5000mL beaker, and then add 500mL of concentrated nitric acid (mass fraction of 68%), and stir well to obtain a dilute nitric acid solution.
[0023] S2, Preparation of scheelite precipitate With a mechanical stirrer installed, dilute nitric acid solution is slowly poured into sodium tungstate aqueous solution under rapid stirring at a speed of about 300 rpm. The solution gradually changes from colorless to milky white, and scheelite precipitate is formed.
[0024] S3, Schistosic acid washing and dispersion The reaction system was filtered and the obtained scheolite precipitate was washed with distilled water at least three times. After drying, the scheolite precipitate was transferred to a beaker containing distilled water and stirred thoroughly to disperse the scheolite precipitate evenly, thus obtaining a scheolite dispersion.
[0025] S4, coordination assembly reaction Sodium silicate (sodium silicate nonahydrate in this example) was added to the scheelic acid dispersion at a silicon to tungsten molar ratio of Si:W = 1:12. After stirring, the turbid liquid became slightly clear. Then, sodium hydroxide was added to adjust the pH of the system to 3-4, and the solution gradually became clear. The solution was heated under reflux for 1 hour to allow the coordination assembly reaction to proceed fully, and a sodium silicotungstate salt solution was obtained.
[0026] S5, Bipolar Membrane Electrodialysis for Acid Conversion The obtained sodium silicotungsten salt solution was passed into a bipolar membrane electrodialysis system for cation exchange treatment for 6 hours to obtain a silicotungsten acid solution. The bipolar membrane electrodialysis system in this embodiment is a common electrodialysis system on the market, and its specific parameters are as follows: Equipment model: BONA-EDB-25S; Membrane stack configuration: A membrane pair is formed by the alternating stacking of a bipolar membrane, a basic separator, a cation exchange membrane, a feed separator, an anion exchange membrane, and an acid separator. Several membrane pairs are stacked together, with polar membranes added on both sides and polar chamber separators to form a membrane stack. Operating voltage 24V; Feed flow rate: For materials, alkaline water should be controlled below 16 LPM, and for electrode water below 8 LPM; Electrolyte in the electrode chamber: 2% sodium chloride; Operating temperature: ambient temperature; Criteria for determining the end point of exchange: After the exchange begins, the conductivity of the material continuously decreases while the conductivity of the alkaline water continuously increases. The end point of exchange is when the conductivity remains unchanged after 6 hours. The conductivity of the material is approximately 15 mS / cm.
[0027] S6, Post-processing The silicotungstic acid solution was evaporated and dried (in this embodiment, the evaporation and drying process was carried out at 80°C and atmospheric pressure) to obtain a pure silicotungstic acid solid product.
[0028] Calculations show that, based on tungsten, the yield of silicotungstic acid in this embodiment is 92.1%.
[0029] Test case The structure, composition and performance of the silicotungstic acid products prepared in the examples were characterized, and compared with standard silicotungstic acid samples.
[0030] Test Example 1 Confirmation of the structure of silicotungstic acid solid products.
[0031] Reference Figure 4 The silicotungstic acid prepared by this invention is a hydrated silicotungstic acid with a Keggin structure. This structure centers on a silicon-oxygen tetrahedron, surrounded by 12 tungsten-oxygen octahedra connected by sharing edges and vertices, forming a highly symmetrical cage-like anionic framework. Hydrogen ions are bound outside the framework as balancing cations, and several water molecules of crystallization are attached to form hydrated silicotungstic acid. This regular cage-like structure is the structural basis for the unique acidity, redox properties, and catalytic performance of silicotungstic acid.
[0032] Reference Figure 5 The silicotungstic acid sample obtained by this invention has a chromium content of 982 cm⁻¹. -1 924cm -1 782cm -1 Three typical characteristic absorption peaks appeared, corresponding to the antisymmetric stretching vibration of the terminal W=O bond, the stretching vibration of the bridging WOW bond, and the stretching vibration of the Si-O bond, respectively. The peak position, peak shape, and relative intensity of each characteristic peak were highly consistent with the infrared spectrum of the silicotungstic acid standard sample, indicating that the functional group structure of the prepared product is consistent with that of the standard silicotungstic acid and has a typical Keggin-type silicotungstic acid structure.
[0033] Reference Figure 6 The characteristic diffraction peaks of the silicotungstic acid sample prepared by this invention are sharp and clear, indicating that the product has good crystallinity. The difference between the peak position and relative intensity of each major diffraction peak and the XRD pattern of the silicotungstic acid standard sample is mainly attributed to the difference in the water of crystallization content between the two, which can be further confirmed by thermogravimetric analysis.
[0034] Reference Figure 7 The silicotungstic acid sample prepared by this invention has a density of 1001 cm⁻¹. -1 977cm -1 925cm -1 549cm -1 226cm -1Five characteristic absorption peaks were observed, corresponding to the antisymmetric stretching vibration of the W=O terminal oxygen, the stretching vibration of the WOW bridging oxygen, and the bending vibration of the polyhedral framework in the Keggin structure, respectively. The positions and shapes of the above characteristic peaks were completely consistent with the Raman spectra of the silicotungstic acid standard sample, confirming the Keggin-type silicotungstic acid structure of the product at the molecular vibration level.
[0035] Reference Figure 8 The thermogravimetric analysis of the samples of this invention is from room temperature to 600°C. o C mainly exhibits two stages of weightlessness. The first stage of weightlessness occurs from room temperature to 200°C. o C, the weight loss is approximately 3.0%, mainly attributed to the removal of water of crystallization molecules; the calculated number of water molecules of crystallization is approximately 5. The second step resulted in a weight loss of 200-550. o C, weight loss is approximately 1.2%, corresponding to H4SiW 12 O 40 Neutrons are removed as structural water; therefore, thermogravimetric analysis indicates that the molecular formula of the sample prepared in this invention is H4SiW. 12 O 40 ·5H₂O. Unlike the standard sample, from room temperature to 600°C... o C exhibits three steps of weightlessness, including the transition from room temperature to 200°C. o The first and second steps of weight loss in C correspond to the loss of water of crystallization, with a total weight loss rate of 10.6%, which corresponds to approximately 19 molecules of water of crystallization. Meanwhile, the weight loss in the 200-500... o The third step of weightlessness in C also corresponds to H4SiW 12 O 40 Neutrons are removed as structural water; therefore, the molecular formula corresponding to the standard sample should be H4SiW. 12 O 40 ·19H2O.
[0036] Reference Figure 9 The silicotungstic acid sample prepared by this invention shows only a single electrophoretic peak, and the peak time and peak shape are completely consistent with the silicotungstic acid standard sample. This indicates that the product contains only the target anion component silicotungstic acid ion, without other heteropoly acid anions or impurity anions. The product has a single phase and the synthesis reaction has good selectivity.
[0037] Test Example 2 Elemental composition analysis of silicotungstic acid solid products.
[0038] Reference Figure 10The energy dispersive spectroscopy (EDS) of the sample from this invention detected only Si, W, and O elements, with no characteristic peaks for other impurity elements. Quantitative calculations showed that the atomic molar ratio of silicon to tungsten in the product was 1:12.02, which is highly close to the theoretical stoichiometric ratio of silicotungstic acid (Si:W = 1:12), demonstrating that the method of this invention can precisely control the silicon-tungsten ratio in the product, resulting in a uniform and stable product composition. In contrast, the atomic molar ratio of silicon to tungsten in the corresponding standard sample was 1.72:25.98 (i.e., 0.8:12), with a silicon content significantly lower than the theoretical value. This may be because the standard sample was prepared using the ammonium metatungstate method, and some silicon failed to be successfully introduced into the metatungstate polyanion, leading to a lower silicon content, i.e., a small amount of metatungstate impurities were present in the standard sample.
[0039] Test Example 3 Reaction process tracking.
[0040] Reference Figure 11 The initial scheelite and metatungstate both have a starting point of approximately 950 cm⁻¹ -1 A broad absorption peak of W=O bond exists at the scheelite system; after adding sodium silicate to the scheelite system, the original broad peak gradually disappears, and the spectral characteristics change significantly; after adjusting the pH with sodium hydroxide and heating under reflux, the spectrum gradually evolves towards a sharp characteristic peak; finally, after pH adjustment, the spectrum reaches approximately 980 cm⁻¹. -1 A sharp characteristic peak of Si-O bond appears at 1001 cm⁻¹. -1 A sharp characteristic peak of W=O terminal oxygen appears at the position, almost completely overlapping with the Raman spectrum of the silicotungstic acid standard sample. This result visually demonstrates the reaction process of scheelitic acid transforming into silicotungstic acid through stepwise coordination assembly, indicating that the highly reactive structural characteristics of scheelitic acid are conducive to the insertion of silicon-oxygen tetrahedra and the formation of a regular Keggin structure.
[0041] Test Example 4 Molybdenum impurity tolerance test.
[0042] Reference Figure 12 , Figure 12 The image shows the energy dispersive spectroscopy (EDS) elemental analysis of the product prepared from sodium molybdate-doped raw material. This sample was prepared using sodium tungstate doped with sodium molybdate as raw material via the scheelitic acid method of this invention. As shown in the image, the atomic percentage of molybdenum in the product is only 0.16%, far lower than the theoretical atomic percentage of 3.24% for molybdenum in the raw material. Calculations show that the process of this invention can achieve a molybdenum impurity removal rate of 95.06%. These results demonstrate that the scheelitic acid method of this invention possesses excellent impurity selectivity, effectively avoiding the co-introduction of associated molybdenum from tungsten raw materials. Even with molybdenum impurities in the raw material, high-purity silicotungstic acid products can still be obtained, reducing the purity requirements of upstream raw materials.
[0043] The embodiments shown in this specification are only used to illustrate the technical solutions of the present invention and are intended to help those skilled in the art understand the principles and advantages of the present invention. They do not constitute a limitation on the scope of protection of the present invention. Although the present invention has been specifically described, those skilled in the art can still make any modifications, equivalent substitutions or other reasonable variations to the implementation methods without departing from the spirit and scope of the present invention. All equivalent technical solutions resulting therefrom should be considered within the scope of protection of this patent.
Claims
1. A method for preparing silicotungstic acid using the scheelic acid method, characterized in that, Includes the following steps: 1) Prepare an aqueous solution of sodium tungstate and react it with dilute acid to form scheelic acid precipitate. After separation and washing, disperse the scheelic acid in water to obtain a scheelic acid dispersion. 2) Add sodium silicate to the scheelic acid dispersion, control the molar ratio of silicon to tungsten to be 1:12, adjust the pH of the system to 3-4, heat and reflux to react, and obtain sodium silicotungstate solution; 3) The sodium silicotungstic acid solution is passed into a bipolar membrane electrodialysis system for cation exchange to obtain a silicotungstic acid solution.
2. The method for preparing silicotungstic acid by the scheelite method according to claim 1, characterized in that, In step 1), the sodium tungstate is sodium tungstate dihydrate; The dilute acid is either dilute nitric acid or dilute sulfuric acid.
3. The method for preparing silicotungstic acid by the scheelite method according to claim 1, characterized in that, In step 1), dilute acid is slowly added to sodium tungstate aqueous solution, and the reaction is carried out under continuous stirring at a speed of 280-320 rpm. The scheelite precipitate was separated by vacuum filtration and washed with distilled water at least three times.
4. The method for preparing silicotungstic acid by the scheelite method according to claim 1, characterized in that, In step 2), sodium hydroxide is used to adjust the pH of the system to 3-4.
5. The method for preparing silicotungstic acid by the scheelite method according to claim 1, characterized in that, In step 2), the heating reflux reaction time is 0.8-1.2 h.
6. The method for preparing silicotungstic acid by the scheelite method according to claim 1, characterized in that, In step 3), the cation exchange treatment time of the bipolar membrane electrodialysis system is 5-7 hours.
7. The method for preparing silicotungstic acid by the scheelic acid method according to claim 1, characterized in that, In step 3), the obtained silicotungstic acid solution is evaporated and dried to obtain a solid silicotungstic acid product.
8. A silicotungstic acid, characterized in that, The silicotungstic acid is prepared by the method according to any one of claims 1 to 7, wherein the silicotungstic acid is a hydrated silicotungstic acid H4[Si(W3O) with a Keggin structure. 10 )4]·nH2O, the molar ratio of silicon to tungsten is 1:(12±0.05).